Fatty acid composition of cultured butter produced using mesophilic and probiotic cultures - Мусий, Любовь Ярославовна; Цисарык, Орыся Иосифовна; Голубец, Ольга Валерьевна; Шкаруба, Сергей Николаевич (Eastern-European Journal of Enterprise Technologies, 2014)
The aim of the research was to study the possibility of modeling the composition of fatty acids by lactic acid bacteria in the production of cultured butter. For the cream culturing, fermenting compositions DVS (Chr.Hansen, Denmark) FloraDanica (FD) and Lbm. acidophilum La-5 (La-5) were used. Four groups of cultured butter were produced: I (samples K1, K2, K3 using FD; FD+La-5; La-5) - cream culturing at a temperature of 30ºC; II (K4, K5, K6 using FD; FD+La-5; La-5) - cream culturing at a temperature of 37ºC; III (K7, K8, K9 using FD; FD+La-5; La-5) - physical ripening 8ºC (2 hours) → biological ripening 20ºC (8 hours) → 12ºC (10 hours); IV (K10, K11, K12 using FD; FD+La-5; La-5) - introducing fermenting compositions in butter granule. Sweet butter served as control (S). Fatty acid composition was examined by gas-liquid chromatography method on a gas chromatograph HewlettPackard HP - 6890. Modeling the fatty acid composition of milk fat lipids in order to increase the trans-11 isomers of fatty acids, endowed with various positive biological properties, is an important scientific task today. Accordingly, modeling the fatty acid composition of butter as the product, which is a milk fat concentrate using the capabilities of lactic acid microflora is of scientific and practical interest. It was found that the cream culturing affects the isomeric composition of fatty acids. The content of the amount of trans-11 fatty acid isomers was the highest (7.92) in K2 in comparison to 7.56% in S (p<0.05), including cis-9, trans-11 C18:2, reaching the maximum in K2 (p <0.05). The content of trans-11 C18:1 has increased from 5.19 in S to 5.28-5.41% in cultured butter samples, the highest was in K2 (p<0.05). The content of the amount of trans-9 isomers was 1.22 in S, whereas in K2, it was the lowest - 1.02%. The results of the content of trans-11 isomers in cultured butter samples suggest that at the joint culturing of FloraDanica and Lactobacillus acidophilus they can be synthesized by lactic acid bacteria, culturing temperature plays an important role in this case.